Environmental Assessment of an Abandoned Briquette Factory – A Case Study at Nagymányok Area, Former Industrial Zone - Halász, Amade; Dezső, József; Poor, Viktoria (Quaestiones Geographicae, 2016)
The study is focused on environmental assessments of impacts by former briquette factory at the Nagymányok area in South Hungary. The (former) industrial zone is located in a northern valley of the Eastern Mecsek Mountains. Until the 1990s this company was the largest briquette factory in Hungary and the demolition works are still incomplete. former investigations were based on only five samples. our sampling sites were selected on the basis of the source of the contaminations and then we covered the whole area in equal distribution. We used the A1-F6 codes for the sample places. We have started from southwest to northeast. The samples were analyzed for Total Petrol Hydrocarbons (TPHs), Polycyclic Aromatic Hydrocarbons (PAHs) and for heavy metals. The area was heavily contaminated by TPHs and moderately heavy metals (such as Cu, Cr, Zn and Pb). Highest contaminant concentrations were found around the former industrial buildings, especially between the boiler-house and the coal-pillbox. In the industrial area the mean of the detected values is below the upper limit of the legal exposure values, but among the former industrial buildings higher (e.g. toxic level) concentration values were detected in multiple samples. Based on our investigation the pollutant can be transported by wind or by water on the surface (stream bed) or underground. The hazardous material can easily reach some part of the city, therefore reclamation is necesarry.